Linguistic Analysis of Phraseological Units Expressing the Concept of “Smile” (English Language as an Example) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the concept and its definition. In addition, a linguistic analysis of phraseological units made with the help of lexemes representing the concept of “smile” was carried out and divided into positive and negative groups in terms of meaning. Also, the translation of English phraseological units into Uzbek language is presented. The obtained results show that there is still an abstraction in the minds of Uzbek-language-speaking people regarding the use of synonymous expressions and there is a need to study the expressions from the pragmatic aspect in the context of communication.